Modelling VARTM process induced variations on bending performance of composite Omega beams - Zeng, Xuesen; Schubel, Peter J.; Lorrillard, Julien (Elsevier, 2016)
Finite element simulation with cohesive contact is presented, to correlate the vacuum assisted RTM process and the bending performance of Omega beams. The model considers the process induced variations, including part thickness, resin rich pockets and voids. The bending performance prediction relies on cohesive contact to model delamination initiation and propagation. Computing efficiency is achieved by mesh scaling. The modelling approach applies to three variations of Omega beams with the different mode-mixture ratios. The finite element predictions result in a high degree of agreement with the experimental measurements.